2016
DOI: 10.4283/jmag.2016.21.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Characteristics and Temperature on Shear Yield Stress of Magnetorheological Fluid

Abstract: Aiming to improve the shear yield stress of magnetorheological fluid, magnetorheological fluids with different particle characteristics are prepared, and the influence rules of particle mass fraction, particle size, nanoparticles content and application temperature on shear yield stress are investigated. Experimental results indicate that shear yield stress increases approximate linearly with the enhancement of particle mass fraction. Particle size and the nanoparticles within 10% mass fraction can improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…This behavior is attributed to the disc shape of the FS particles. The particle shape determines the sedimentation velocity and hence the suspension’s stability. The terminal velocity of a particle in a fluid can be defined as follows: where Re is the Reynolds number based on the equivalent spherical diameter of a particle, C D is the drag coefficient, ρ f is the density of the liquid medium, ρ s is the density of the solid particle, g is gravitational acceleration, and μ is the liquid medium viscosity. ,, Then, the terminal velocity ratio between BS and FS is approximated as where we neglect the small density difference between FS and BS. At low Reynolds number, the drag coefficient for a sphere is C D = 24/Re; for a nonspherical particle, C D = 24* (1+ 0.18 * Re FS 0.65 ) /Re FS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is attributed to the disc shape of the FS particles. The particle shape determines the sedimentation velocity and hence the suspension’s stability. The terminal velocity of a particle in a fluid can be defined as follows: where Re is the Reynolds number based on the equivalent spherical diameter of a particle, C D is the drag coefficient, ρ f is the density of the liquid medium, ρ s is the density of the solid particle, g is gravitational acceleration, and μ is the liquid medium viscosity. ,, Then, the terminal velocity ratio between BS and FS is approximated as where we neglect the small density difference between FS and BS. At low Reynolds number, the drag coefficient for a sphere is C D = 24/Re; for a nonspherical particle, C D = 24* (1+ 0.18 * Re FS 0.65 ) /Re FS .…”
Section: Resultsmentioning
confidence: 99%
“…where Re is the Reynolds number based on the equivalent spherical diameter of a particle, C D is the drag coefficient, ρ f is the density of the liquid medium, ρ s is the density of the solid particle, g is gravitational acceleration, and μ is the liquid medium viscosity. 32,42,43 Then, the terminal velocity ratio between BS and FS is approximated as where D FS is the equivalent sphere diameter. Therefore,…”
Section: Magnetorheologicalmentioning
confidence: 99%
“…This is a still controversial subject that needs to be studied further. 44,45 The HRTEM result indicates that the transformation of the multidomain cubic particles into single domain crystalline may not be the reason for the low yield stress value of the cubic Fe 3 O 4 particles at low magnetic field strength (Figure 10b). Instead of the domain change from the multidomain structure into the single domain, the different trends of the yield stress at low and high magnetic field strengths are due to the particles volume effect that the large sizes of the cubic Fe 3 O 4 particles compared to that of f-PS/Fe 3 O 4 nanoparticles need higher magnetic field strength for the polarization.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%
“…Export boundary. The coefficient of the temperature field composite heat transfer of the MRF yield stress testing device 16 reflects the effects of convective and radiation heat transfers.Therefore, the composite heat transfer coefficient a = 9.7 W/m 2 K is obtained combined with the calculation result of heat transfer between the stationary surface and the surrounding air of equation (9).…”
Section: Simulation Calculation and Experimentsmentioning
confidence: 99%
“…The test results of Weiss 8 show that yield stress decreases with School of Mechanical and Automotive Engineering, Shanghai University of Engineering Science, Shanghai, China increasing temperature. Wu et al 9 pointed out that when the temperature is higher than 100°C, shear yield stress rapidly decreases due to thermal expansion and thermomagnetization effects. Rabbani et al 10 showed that the maximum yield stress sharply increases with the decrease of temperature in their study on MRF stability and rheological properties.…”
Section: Introductionmentioning
confidence: 99%